Symposium: Courts, Judges, Politics—Some Political Science Perspectives - Lucius J. Barker (Washington University Law Quarterly, 1971)
Unlike most symposia, this one is not restricted to a single topic. The common theme of this endeavor, and there is even an exception to this, is that the research and ideas presented are those of professionally trained political scientists. But the exception—a contribution by a recent law school graduate—underscores the basic purpose of this Symposium: to show the insights and values that can be gained by examining a variety of topics from social science perspectives.